'It's Like Biting Your Own Tail': Pedro Lemebel's Queer Response to the Challenge of Subversion in Neoliberal Times. Issue 2 (3rd April 2018) - González, Melissa M.
Abstract : Using the methods of textual analysis and in conversation with both Latin American cultural studies and queer studies, the essay examines the ways that Pedro Lemebel's diverse body of work – ranging from live performances, fiction, non-fictional crónicas, and interviews – engages the limits of subversion in neoliberal times. On the one hand, Lemebel's work has been routinely framed in terms of its subversion of gendered, sexual, and political norms. On the other hand, scholars and commentators have not deeply engaged the many ways that Lemebel's own work comments on and represents the challenges of producing subversive cultural productions in a globalized, late capitalist environment in which subversion, including his own, can be undone precisely when it is most celebrated, valued, and commodified. Reading Lemebel's commentaries and interviews as producing cultural criticism that complements his better-known crónicas' and performances' ideological narratives, the essay argues that Lemebel's oeuvre repeatedly addresses the challenges of performing a delicate dance between resistance and co-optation, given his acknowledged inseparability from the market. Taking Lemebel as a model for this balancing act, the essay ultimately aims to reveal and critique some of the ways that we academics tend to read sexual dissidence as successful subversion without recognizing its complications and limits.